A comparative study on LinkedIn and Sina Weibo users’ perceptions of the carbon-neutral city - Zeng, Liyun; Li, Rita Yi Man; Mao, Yunyi; Chen, Hong; Zeng, Huiling (Frontiers in Environmental Science, 2022)
A carbon-neutral city is one of the most critical topics in carbon neutrality. To study the general public and professionals’ focus, we analysed the posts on Weibo and LinkedIn. Active users and institutions were analysed through Pycharm, Navicat Premium, KHCoder, and Tableau. This study included 1908 microposts (14668 sentences) on Weibo and 533 posts (3733 sentences) on LinkedIn. On Weibo, the most influential users were governments and organisations; for example, Baotou Daily, Beijing Ecological Environment, 922 Green Travel, Baotou Evening News, and Baoding Evening News. On LinkedIn, the most influential person was the co-director of Carbon Neutral Cities Alliance. The most popular topics on LinkedIn included “city”, “carbon”, “climate”, “neutral”, “energy”, “emission”, “sustainability”, “sustainable”, “neutrality” and the keywords of “world”; while “carbon”, “city”, “energy”, “development”, “new”, “green”, “promote”, “neutrality”, “construction” and “industry” are more prevalent in Weibo. Both LinkedIn and Weibo users focus on “energy” and global carbon emission problems. LinkedIn users mentioned “climate” and “sustainability” most in their posts, but Weibo users concerned about green development in the construction industry.